Congenital and perinatal infections : prevention, diagnosis and treatment - McIntyre, James (James A.); Newell, Marie-Louise (Cambridge University Press, 2000)
Congenital and perinatal infections remain a stubborn and major cause of morbidity and mortality in infants throughout the world. This concise, accessible account provides an essential guide to the diagnosis, management and prevention of these infections. The first three chapters underline how and why infections during this critical period can be so devastating. The main section of the book focuses on individual infections, and emphasises effective intervention based on the very latest knowledge and techniques. Another unique feature of this account is its recognition that the severity and types of these infections vary considerably from country to country, and from the developing world to the developed world: the international team of experts involved in this compilation have striven to make this an account that will transcend these boundaries and be suitable for all doctors and allied health professionals around the world charged with the care of the mother and newborn.